Aktivitas antioksidan krim kombinasi ekstrak Eucheuma Cottonii Sumbawa dan ekstrak Citrus lemon L. impor dengan metode DPPH - Dwi Kurniawati Sambodo; Nandia Arlesia (Health Sciences and Pharmacy Journal, 2019)
Cerrenty, The high exposure for free radicals has a negative impact on the health and aesthetics of the skin, especially facial skin, because it requires cosmetic that contain antioxidants to counteract and reduce the negative effects of it. Eucheuma cottonii and Citrus lemon L have bioactive compounds that have the potential as antioxidants. This research was conducted to find out antioxidant activity and the most optimal formula of the three cream formulas by DPPH method. Eucheuma cottonii and Citrus lemon L peel were extracted by remaseration method. The cream is formulated in 3 formulas with a ratio of extracts of 1: 2, 2: 1, and 1: 1 in 100 grams of cream with positive control of vitamin C. The three formulas were tested qualitatively and quantitatively by DPPH method with spectrophotometry visible at maximum wavelength 517 nm uses IC50 value. Qualitative test shown that the three cream formulas had antioxidant activity by DPPH damping which were characterized by reduced intensity of purple color. Quantitative test results in IC50 value formula 1 was 11251.5 ppm, formula 2 was 8592.2 ppm, and 10025.5 ppm for formula 3. From too  concluded that the three creams have antioxidant activity and formula 2 has the most optimal antioxidant than 2 other formulas